On the use of Some Heterocyclic Compounds as Anti - Fire to Improve the Properties of Composite Polymer - nihad abed, Foud; amer mahdi, Saif; naji rashid, Sahar (International Journal of Engineering and Technology, 2018)
In this study, a number of thiazol compounds were prepared and were diagnosed with infrared techniques, NMR spectrum and C13NMR spectroscopy and measurement of the melting point where results were shown to be consistent with what was published in the literature. These compounds were used as anti-fire agents to inhibit the insoluble polysaccharide resin used in the construction process, which is highly flammable. ASTM E 285-80 was used in this specification. Unsaturated polystyrene sheets were used with dimensions of cm15 cm, The width of cm2, thickness of mm4) and the percentage added of each of the prepared compounds (0.51%) The results obtained from the standard (ASTM E 285-80) that the compound (1) had the best results from the other compound, It showed high efficiency as an anti-fire additive by significantly reducing the combustion time, and for the other compounds.